GENETIC ARCHITECTURE AND ASSOCIATION ANALYSIS IN BITTER GOURD (MOMORDICA CHARANTIA L.) LANDRACES - MANEESH KUMAR SINGH; D. R. BHARDWAJ; D. K. UPADHYAY (The Bioscan, 2012)
The nature and magnitude of genetic diversity were estimated in 25 bitter gourd genotypes on 10 quantitative traits during the summer season under indo-gangetic plains of eastern Uttar Pradesh, so as to identify promising traits on which selection can be made. The experiment carried out following randomizing block design with three replications results indicted that high phenotypic and genotypic coefficients of variation were found for fresh fruit yield per plant followed by fruit length, fruit width and number of fruits per plant, indicating high genetic variability in these traits. High heritability coupled with high genetic advance as percent of mean was observed for fruit length, yield per plant, fruit diameter, fruit weight, branch per plant and seeds per fruit, indicating the possible role of additive gene action. The path coefficient analysis based on fruit diameter as a dependent variable implicated that plant height had the highest positive direct effect on fruit yield. The emphasis should be given to improve fruit yield per plant in bitter gourd, focus should be given on fruit weight, fruit length, fruit diameter and plant height as it has positive correlation with fruit yield per plant.